2021
DOI: 10.1155/2021/4836804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of b Value on Imaging Quality for Diffusion Tensor Imaging of the Spinal Cord at Ultrahigh Field Strength

Abstract: Objective. To explore the optimal b value setting for diffusion tensor imaging of rats’ spinal cord at ultrahigh field strength (7 T). Methods. Spinal cord diffusion tensor imaging data were collected from 14 rats (5 healthy, 9 spinal cord injured) with a series of b values (200, 300, 400, 500, 600, 700, 800, 900, and 1000 s/mm2) under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In the literature, this is more evident at the low field strength of the MR scanner as 1.5 T [75], and only 10% of the selected studies of this review used this field, less evident in high field strength (3 T and 7 T) due to their relatively high SNR, in which the increase in b value has little influence on the decrease in SNR, showing the best image and data quality with the respective b-values, 200 and 900 s/mm 2 [73]. The selected studies included in this review reported normally more than one b-value and the MRI of 1.5T used b-values ranging from 800 to 1000 s/mm 2 and the 3 T from 700 to 5000 s/mm 2 [73,74].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In the literature, this is more evident at the low field strength of the MR scanner as 1.5 T [75], and only 10% of the selected studies of this review used this field, less evident in high field strength (3 T and 7 T) due to their relatively high SNR, in which the increase in b value has little influence on the decrease in SNR, showing the best image and data quality with the respective b-values, 200 and 900 s/mm 2 [73]. The selected studies included in this review reported normally more than one b-value and the MRI of 1.5T used b-values ranging from 800 to 1000 s/mm 2 and the 3 T from 700 to 5000 s/mm 2 [73,74].…”
Section: Discussionmentioning
confidence: 92%
“…The acquisition parameters of the DTI is important because they affect values of white matter (WM) scalar metrics, including FA, MD, Signal Noise Ratio (SNR), and even entire brain tractography investigations. These acquisition parameters include the diffusion sensitivity coefficient (b-value), which is a factor that reflects the strength and timing of those gradients used to generate DWI, as well as the reliability of DTI results concerning image and data quality; diffusion directions, in which there are more directions the longer the acquisition time; and voxel size (the smaller the size, the higher the quality [72,73]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation